2016
DOI: 10.5301/ejo.5000832
|View full text |Cite
|
Sign up to set email alerts
|

Is Artificial Reproductive Technology a Risk Factor for Retinopathy of Prematurity Independent of the Generation of Multiple Births?

Abstract: Purpose: There is some debate regarding whether artificial reproductive technology (ART) constitutes an independent risk factor for retinopathy of prematurity (ROP). We wanted to assess the prevalence of ART in multiple birth infants seen for ROP screening and whether or not ROP was identified or treated, in order to evaluate whether ART contributes a risk factor for ROP independent of the generation of multiple births. Methods:A retrospective audit was performed of all multiple birth babies admitted to a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…ART multiple birth babies make up a considerable proportion of the ROP screening burden, and their number is likely to increase as ART is increasingly available and utilised [ 15 ]. McKibbin et al were one of the first to investigate the workload imposed by the treatment for infertility on a ROP screening programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ART multiple birth babies make up a considerable proportion of the ROP screening burden, and their number is likely to increase as ART is increasingly available and utilised [ 15 ]. McKibbin et al were one of the first to investigate the workload imposed by the treatment for infertility on a ROP screening programme.…”
Section: Resultsmentioning
confidence: 99%
“…They found no significant difference between the numbers of babies developing ROP in the ART vs non-ART groups. However, the estimated odds of developing ROP were slightly higher in the ART babies [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mechanism is not clear, association between assisted reproductive technology (ART) including in vitro fertilization (IVF) and ROP has been studied with conflicting results. 34,67,125,256,259,394 Some studies identified ART as an independent risk factor for ROP, but it is difficult to draw definite conclusions because ART is also associated with factors including low BW, early GA, and multiple births. Two United Kingdom studies suggest that improvements in IVF may have reduced the additional risk of severe ROP.…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…Previous studies have shown multiple pregnancies to be a risk factor of GDM [14]. However, although twin pregnancies are often associated with high risk of cesarean section, pre-eclampsia, hypoglycemia, retinopathy, preterm birth and low birth weight [15][16][17][18][19][20], GDM in twin pregnancies have shown conflicting associations to these adverse outcomes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%